THE ROLE OF MANGROVE URBAN FOREST ECOSYSTEM IN CARBON STORAGE AND POLLUTANT ABSORPTION IN TAMAN WISATA ALAM ANGKE KAPUK, NORTH JAKARTA - Angelina Edi Srigati, Febby
Jakarta, as the capital city of Indonesia, continues to carry out urban development which causes green open spaces to become increasingly narrow, thus having an impact on disrupting the balance of the ecosystem. The mangrove ecosystem in the Angke Kapuk Nature Tourism Park (TWAAK) is an urban forest that plays an important role in storing carbon and absorbing pollutants in Jakarta. This research aims to calculate the estimated potential of stored carbon and the estimated pollutant that can be absorbed by mangrove urban forest at TWAAK, North Jakarta. This study was conducted by taking plots by purposive sampling based on the criteria of canopy density: low dense, moderately dense, and very dense which were analyzed by NDVI (Normalized Difference Vegetation Index). The number of plots taken was 30 plots consisting of 12 very dense plots, 11 moderately dense plots, and 7 low dense plots. Allometric equations are used to calculate carbon storage, while pollutant absorption is calculated using i-Tree Eco software. The results showed that the estimated carbon stored in the mangrove forest of TWA Angke Kapuk was 6,356.32 tons (111.59 tons/ha) with details of carbon storage at very dense plot is 2,289.07 tons (172.37 tons/ha), moderately dense plot is 2,511.60 tons (120.23 tons/ha), and low dense plot is 1,555.65 tons (68.26 tons/ha). The estimated pollutant absorption that can be absorbed by the TWAAK mangrove urban forest is 11.3 metric ton/year with details of pollutant absorption at very dense plot is 6,50 metric ton/year, moderately dense plot is 3,45 metric tons/year, and low dense plot is 1,34 metric tons/year.